PEMBUATAN VIRGIN COCONUT OIL DENGAN METODE PENGGARAMAN - SUSILOWATI, SUSILOWATI (Jurnal Teknik Kimia, 2009)
Palm Oil represent oil of vegetation yielded from coconut krenel. Pursuant to sour content of fatpalm oil is classified into sour oil of laurat. Because the sour content laurat is biggest of ( 44 – 52%)compared to acid of other fat. Virgin Coconut Oil represent palm oil of made purification from flesh of fresh coconut processed without warm-up, so that the important content in oil remain to be defensible. Method of Research run by enhancedly salt CaCOFrom result of research indicate that the best condition got at an addition of salt of CaCO3 equal to 4 gramin day with amount of oil which got as much 69,907 gram with acid contents of laurat equal to 46,23 ( 0,1,2,3,4 gram) into cream of coconut mink 200 gram,then swirled and hushed during ( 2,3,4,5,6 day). Afterwards the oil taken and analysed the sour content of laurat.Keyword: VCO (Virgin Coconut Oil), Salting method